Hubungan Pengetahuan Pencegahan Covid-19 Dengan Latar Belakang Pendidikan Pada Masyarakat Kelurahan Langenharjo: Prevention Knowledge of COVID-19 and Connection with the Education Background of People in Langenharjo Village - Ariani, Rizka; Assyauqy, Muhammad Faruq; Ihsana, Nuni (Ahmad Dahlan Medical Journal, 2023)
Dissemination of COVID-19 being considerable especially in Indonesia with large population. Prevention from this disease need cooperation between government, medic, paramedic, and public concern. Education is the most prominent to understand the spread of this disease. Other factors that influenced the knowledge are media of information, socioeconomic, culture and environment. This study wanted to know the relationship between education background and the knowledge of COVID-19 prevention. The population of this study were 98 respondents with 48 women and 50 men. This study used spearman rank method to analyzed the relationship between education background and knowledge of COVID-19. The result from this study was 5 respondents with poor and fair knowledge and 88 respondents with good knowledge. The relationship between education background and knowledge of COVID-19 prevention was significant. Other factors also had important role in COVID-19 prevention knowledge. In this study, the education background influenced the COVID-19 prevention knowledge of Langenharjo people significantly.